Legality of Digital Contracts in Indonesian Positive Law Perspective - Al Qindy, S.H., M.Kn., Fatria Hikmatiar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
In the rapidly developing digital era, digital contracts have become popular in Indonesia due to their convenience and efficiency in business transactions, such as online buying and selling. A digital contract is an agreement made using electronic or digital media, differing from the traditional paper and pen method. The rise of electronic transactions has led to the creation of digital or electronic contracts, resulting in electronic engagements. This shift from conventional to digital contracts represents technological advancement in contract practices, as seen with Electronic Contracts. Unlike conventional contracts, which have clear legal regulations, Digital or Electronic Contracts in Indonesia are relatively new. This research examines the legality and validity of Digital Contracts from the perspective of Indonesian Positive Law. The study aims to understand and assess the legality of digital contracts in Indonesia. The research employs normative legal research methods, using the Statutory Approach and the Conceptual Approach. The findings conclude that digital contracts are legal and valid under Indonesian positive law, provided they meet the validity requirements of an agreement as stipulated in Article 1320 of the Civil Code.